Dipole source analyses of laser evoked potentials obtained from subdural grid recordings from primary somatic sensory cortex - Baumgärtner, Ulf (American Physiological Society, 2011)
The cortical potentials evoked by cutaneous application of a laser stimulus (laser evoked potentials, LEP) often include potentials in the primary somatic sensory cortex (S1), which may be located within the subdivisions of S1 including Brodmann areas 3A, 3B, 1, and 2. The precise location of the LEP generator may clarify the pattern of activation of human S1 by painful stimuli. We now test the hypothesis that the generators of the LEP are located in human Brodmann area 1 or 3A within S1. Local field potential (LFP) source analysis of the LEP was obtained from subdural grids over sensorimotor cortex in two patients undergoing epilepsy surgery. The relationship of LEP dipoles was compared with dipoles for somatic sensory potentials evoked by median nerve stimulation (SEP) and recorded in area 3B (see Baumgärtner U, Vogel H, Ohara S, Treede RD, Lenz FA. J Neurophysiol 104: 3029–3041, 2010). Both patients had an early radial dipole in S1. The LEP dipole was located medial, anterior, and deep to the SEP dipole, which suggests a nociceptive dipole in area 3A. One patient had a later tangential dipole with positivity posterior, which is opposite to the orientation of the SEP dipole in area 3B. The reversal of orientations between modalities is consistent with the cortical surface negative orientation resulting from superficial termination of thalamocortical neurons that receive inputs from the spinothalamic tract. Therefore, the present results suggest that the LEP may result in a radial dipole consistent with a generator in area 3A and a putative later tangential generator in area 3B.